Content networking architecture, protocols, and practice - Hofmann, Markus. (Morgan Kaufmann series in networking., 2005)
As the Internet has grown, so have the challenges associated with delivering static, streaming, and dynamic content to end-users. This book is unique in that it addresses the topic of content networking exclusively and comprehensively, tracing the evolution from traditional web caching to today's open and vastly more flexible architecture. With this evolutionary approach, the authors emphasize the field's most persistent concepts, principles, and mechanisms--the core information that will help you understand why and how content delivery works today, and apply that knowledge in the future. + Focuses on the principles that will give you a deep and timely understanding of content networking. + Offers dozens of protocol-specific examples showing how real-life Content Networks are currently designed and implemented. + Provides extensive consideration of Content Services, including both the Internet Content Adaptation Protocol (ICAP) and Open Pluggable Edge Services (OPES). + Examines methods for supporting time-constrained media such as streaming audio and video and real-time media such as instant messages. + Combines the vision and rigor of a prominent researcher with the practical experience of a seasoned development engineer to provide a unique combination of theoretical depth and practical application.